O pertencimento docente à ciência que se ensina - uma análise sob a óptica epistemológica prigoginiana - Sousa, Thiago Weslei de Almeida (2023)
In this research, our objective was to defend the thesis that the category of belonging to science, stemming from the epistemological construct of Prigogine, should be considered in propositions within the field of teacher education in Science Education. Its existence directly influences the professional profile adopted by teachers in their teaching practices. This thesis comprises seven articles. In the first article, Possible Contributions of Ilya Prigogine to the Consolidation of a Genuine Philosophy of Chemistry, we highlighted the use of Prigogine as a theoretical reference in the field of Science Education. This article is an integral part of the thesis's history and allowed the researcher to identify the current research problem. The second article, Pleasure, Prigogine!, presents the main contributions of Prigoginian epistemology, along with its principal criticisms, potentialities, and limitations. This article is included in the research because the assimilation of Prigogine's theoretical assumptions was necessary for a thorough understanding of their use during the thesis development. The third article, The Theoretical Assumptions of Ilya Prigogine and Critical Epistemology – A Dialogue of Convergences, demonstrates that Prigogine can be employed as a progressive epistemological theoretical reference. We included this article to investigate if the conceptions of belonging and Education adopted by researchers align with the Prigoginian reference. The fourth article, Analyses and Reflections on the Presence of Prigoginian Epistemological References in Theses and Dissertations in the field of Science Education, aimed to highlight the use of Prigogine as a theoretical reference in the field of Science Education. Through this article, we concluded that, despite its relevance, Prigogine's theoretical framework is underexplored in the domain of Science Education. The fifth article, The Teacher's Belonging to the Science They Teach – An Analysis from the Prigoginian Epistemological Perspective, discussed and problematized the interconnections between belonging, science, and the teacher who imparts this science. This article supported the central thesis discussion, connecting Prigoginian thought to belonging and the science perception of science teachers. In the sixth article, Understanding Epistemological Belonging in Teacher Training Models Synthesized by Contreras, we examined the presence and/or absence of the "belonging to science" category in the three teacher practice comprehension models synthesized by Contreras. This article confirmed our hypothesis of the neglect of the "belonging" category in the mentioned models. Through the construction and presentation of these six articles, we weave a narrative that reinforces our thesis that belonging has the potential to influence teaching professionalism. Finally, we believe that this doctoral thesis, by establishing the work of Prigogine as a new theoretical reference and suggesting various perspectives for research using this theoretical framework, positions our research as an innovation in Science Education and a potential theoretical reference for new research within this field.